A review on High-Temperature Applicability: A milestone for high entropy alloys - Dewangan, Sheetal Kumar; Mangish, Ananddev; Kumar, Sunny; Sharma, Ashutosh; Ahn, Byungmin; Kumar, Vinod (Engineering Science and Technology, an International Journal, 2022)
Due to the limitations of utilizing pure metals, several elements were combined to make an alloy in order to provide and improve certain features as needed for the application. The concept of alloy making has diversified over a thousand years. In addition, A new concept of alloy design has been discovered early decades and named high entropy alloy (HEA). Multiple principal elements are being adopted with a high concentration to develop new material. The multi-dimension composition space has several unrevealed properties that the researchers are exposing. However, an ample number of properties have been uncovered. Despite this, alloys based on intermetallic compounds have developed as high-temperature materials with the primary goal of replacing nickel-based superalloys due to their low melting temperatures. For applications in sensitive environments, there is still a lot of interest, thus these alloys are continuously being developed. Mechanical strength, microstructural stability, and corrosion/oxidation resistance are all requirements for alloys used in high-temperature applications. High entropy alloys may be the primary materials used in aviation turbine engine hot section components and high-temperature environments. Nevertheless, there must be many other concealed properties to date, and it is likely to be discovered soon, seeing the ample research going on it. In this urge, this review explores the up-to-the-minute milestones in the high-temperature application achieved by the HEAs. The conversant assessment also includes different processing routes of HEAs, properties at high temperatures, and advanced HEAs that could be exploited for high-temperature applications. In a nutshell, this artifact emphasizes the potential application of HEAs that could be advanced high-temperature materials in the future. Thus, the review outlines HEAs and covers various advantageous information for working on materials exposed to high-temperature applications.
Keywords: High Entropy Alloy; High-Temperature Properties; Mechanical Properties; Oxidation properties; Refractory high entropy alloy